PENGARUH KUALITAS PRODUK, HARGA DAN LOKASI TERHADAP KEPUASAN KOSUMEN (Studi Kasus Pada Waroeng Spesial Sambal / SS Lampersari Semarang) - Bentar Bentar; Maduretno Widowati (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2018)
This research was conducted in Waroeng SS Lampersari Semarang Branch which aims to know: 1) Influence of Product Quality to Customer Satisfaction. 2) Price Influence on Consumer Satisfaction. 3) The influence of Location on customer satisfaction. 4) The Influence of Product Quality, Price and Location on customer satisfaction.This type of research uses quantitative descriptive. Data collection technique was done by distributing questionnaires. The population in this study are consumers who visit and make purchases at the restaurant Waroeng SS Lampersari with a sample size of 96 respondents and taken by Simple Random Sampling technique. Data analysis techniques used are multiple linear regression analysis, t test, F test and R2 test.The result of regression analysis obtained the equation Y = 5,621 + 0,233X1 + 0,496X2 + 0,331X3. This equation shows consumer satisfaction is influenced by product quality, price and location. Based on test results t: 1) Product Quality positively affects customer satisfaction. This is evidenced by the t count> t table or 2.644> 1.985 and the significance value of 0.010 <0.05 then it can be concluded Ho rejected and Ha accepted. 2) Price has a positive effect on customer satisfaction. This is evidenced by the t count> t table or 2.840> 1.985 and the significance value of 0.006 <0.05 then it can be concluded Ho rejected and Ha accepted. 3) Location has a positive effect on customer satisfaction. This is evidenced by t arithmetic> t table or 2.144> 1.985 and the value of significance 0.035 <0.05 then it can be concluded Ho rejected and Ha accepted. 4) Product Quality, Price and Location simultaneously or together affect consumer satisfaction. It is proved based on the result of F test known that F-count> F-table is 35,679> 2,70 with significance value 0,000 <0,05.